Application of the elements of the Industry 4.0 concept in chemical industry and comparison with other industrial areas in the Czech Republic - Košťálová, Jana; Vávra, Jan; Bergerová, Veronika (University of Pardubice, 2020)
Information and Communication Technologies (ICT) is one of the most dynamic developed areas, opening new business models and impacting efficiency and productivity. The use of ICT technology and its outcomes in other economic areas and their overall social impact is desirable to be continually evaluated. Intensive ICT developments is named as Industry 4.0 or the fourth industrial revolution, including the deployment of integrated ICT solutions, digitization, automation, robotics, intensive use of the Internet, including the Internet of Things or the Internet of Services, cyber-physical systems and artificial intelligence systems, additive printing, and other tools. The aim of the article is to determine the basic elements of Industry 4.0 and assess their use and impact on society; such an assessment being carried out in selected companies of the chemical, food, and automotive industry of the Czech Republic. The above industries are using automated systems available already for years. The specific use of elements of Industry 4.0 is influenced by industry specifications, both by using these elements and gradually introducing them to be adapted for expected conditions. In the chemical industry, the elements of Industry 4.0 are used; especially, in the digitization of the assesment of the value chain from the design phase of the product up to its production, management, and logistics. There are used elements that contribute to increased productivity, production planning tools and supply optimization. For monitoring and controlling of operational safety production operations data, such as data distributed via the Internet of Things, are shared and analyzed. Similar situation is in the food industry, whereas in the automotive industry, it is possible to take advantage of digitalisation and robotization. Based on the analysis reported herein, the situation in selected enterprises of the chemical, food and automotive industries is evaluated, a number of elements of Industry 4.0 presented and the expected trends of further development in this area outlined.
Keywords: Industry 4.0; information and communication technologies; industry; chemical industry; food industry; automotive